Padrão epidemiológico e operacional da vigilância dos agravos à saúde do trabalhador nos sistemas de informação em saúde no estado do Ceará de 2010 a 2018 - Souza, Denise Coelho de (2020)
Work accidents (TA) are sudden events that cause damage to the health of workers, and worldwide, they are responsible for the largest number of deaths or serious disabilities. Within this context, TA are considered of great epidemiological importance, since they have an important social and economic relevance. In Brazil, the Northeast occupies the third position in the ranking of TA, and Ceará also occupies the third position in the ranking when compared to the other states that compose its region. A factor that further aggravates this situation is that countless problems contribute to the underreporting of TA, this causes a difficulty in planning, implementing and evaluating the services of the Occupational Health Surveillance. Given this problem, this study aimed to carry out an assessment of the epidemiological and operational pattern of surveillance of serious and fatal occupational accidents in health information systems in the State of Ceará between the years 2010 to 2018. It has an ecological design with observation of the temporal variation longitudinal and spatial. Results: 20288 notifications of ATGF were identified, the highest percentage in the Fortaleza macro-region with 53.6% of the notifications, 89% of whom were male between the ages of 30 and 49 years old and had completed elementary school with 38.8%. The situation in the labor market for the injured concentrated on registered employees, 41.2% and the most frequent type of accident was the typical accident with 62.7%, where 50.8% was not issued to CAT, and the body part most affected was the hand with 31.3% in workers whose occupation had occurred on a larger scale in service workers with 29.6% followed by workers in agricultural and forestry exploration and mechanization with 12.5%. The CI tended to increase over the study period, with a variation of 150.7%. The mortality rate fell between 2010 and 2012, followed by an increase of 43% from 2014 to 2018. The mortality rate, on the other hand, decreased throughout the study period. The underreporting of simultaneous deaths by TA in SINAN was higher than in SIM, respectively 66.12% and 33.87%. The basic cause of non-simultaneous deaths by TA from SINAN in SIM, were external causes, with a percentage of 95.2%. Regarding the incompleteness of the variable “work accident”, SIM registered 97.6%, and the five macro regions of the State remained above 95.9%, whereas in SINAN, the variable that had the best performance was the aggravation of accidents by venomous animals with only 9.4%, and worse performance with exogenous intoxications with 77.6%. In the “evolution” variable, incompleteness was greater in exogenous intoxications, with 36.5% and the best performance was concentrated in ATGF with 6.7% and accidents with venomous animals with 7.3%. Conclusion: The study contributes to the knowledge of the reality and situational diagnosis of epidemiological and operational aspects related to serious and fatal occupational accidents in the State of Ceará, giving VISAT support to be able to plan and propose the necessary interventions. Priority actions, such as the reaffirmation and awareness of professionals of the importance of notification and the complete filling of the notification and DO form, as well as an improvement in the interaction between the systems and professionals that feed SINAN and SIM, must be taken into account. Improve data quality and qualification. Regarding the incompleteness of the variables “work accident” and “evolution”, exogenous intoxications need a special vigilance look, since this condition presented the worst performance of completeness among the health problems. SINAN analyzed in the study. In the macro regions of the State of Ceará, however, some need a more priority look, since some regions did not present a good performance of completeness throughout the study period in the SINAN diseases (ATGF, exogenous intoxication and accidents by venomous animals) and SIM.